College women's sexual and reproductive health screening behaviors and the role of mother–daughter communication. Issue 4 (18th May 2020) - Gibson, *Laurel P.; Denes, Amanda; P. Crowley, John
Abstract: Objective: The study investigated the role of mother–daughter communication and race in college women's decisions to pursue sexual health screening services. Participants: Participants were 301 college women who primarily identified as White and Asian American (Mage = 19 years). Methods: Participants completed an online survey that assessed mother–daughter communication about sex and responded to items pertaining to pursuing sexual health screening services. Results: Maternal communication predicted daughters' screening behaviors and sexual anxiety mediated the negative association between conservative communication from mothers and screening behaviors. Asian American college women were less likely than White college women to report that they received frequent and open communication about sex from their mothers and reported higher levels of sexual anxiety. Conclusions: Mothers should be aware of the implications their communication patterns may have on their daughters' sexual and reproductive health, and college women's sexual anxiety should be addressed in order to increase utilization of screening services.